Homem internauticus: reflexões sobre juventude(s), influencers digitais e estéticas da masculinidade através de perfis do Instagram - Figueiredo, Drielly Elienny Duarte de (2022)
The present work aims to bring forth a discussion concerning how masculinity aesthetics are perceived, constructed and undertaken by youth through social media. In here, we are regarding Millennials and Gen Zers as “youth”, groups that are also known as digital natives of first and second generation. It is from them that the figure of the digital influencers, interlocutors of this research, emerges in society. Thinking of the reach and the role that online content producers (influencers) have in a consuming society, we try to draw a line of understanding about how and to what extent these professionals contribute to the construction of new aesthetic identities of masculinity. As this is a research on digital influencers, we took the digital platform Instagram as our field, where we observed the profiles of every interlocutor, their posts, interactions with their followers and brief interactions via private messaging; we have also used Google Meet for longer interviews. In our final considerations, it is possible to understand the role digital influencers have in the construction of new forms of masculinity in the consuming society, mainly with regards to Millennials and Generation Z, demographics that were addressed in this research.